2011
DOI: 10.1158/0008-5472.can-10-0730
|View full text |Cite
|
Sign up to set email alerts
|

Src and Caveolin-1 Reciprocally Regulate Metastasis via a Common Downstream Signaling Pathway in Bladder Cancer

Abstract: In bladder cancer, increased Caveolin-1 (Cav-1) expression and decreased Src expression and kinase activity correlate with tumor aggressiveness. Here, we investigate the clinical and functional significance if any, of this reciprocal expression in bladder cancer metastasis. We evaluated the ability of tumor Cav-1 and Src RNA and protein expression to predict outcome following cystectomy in 257 patients enrolled in two independent clinical studies. In both, high Cav-1 and low Src levels were associated with met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 43 publications
(60 reference statements)
4
70
0
Order By: Relevance
“…52 Caveolin-1 expression is correlated with tumor stage and grade of bladder transitional cell carcinoma (TCC). 53,54 Caveolin-1 expression was correlated significantly with T stage and grade of bladder TCC, which strongly indicates that caveolin-1 is involved in tumor progression and that the increased expression of caveolin-1 is a late event in urothelial carcinomas. 55 The increased expression of caveolin-1 is associated with tumor progression and poor prognosis in Figure 11.…”
Section: Discussionmentioning
confidence: 91%
“…52 Caveolin-1 expression is correlated with tumor stage and grade of bladder transitional cell carcinoma (TCC). 53,54 Caveolin-1 expression was correlated significantly with T stage and grade of bladder TCC, which strongly indicates that caveolin-1 is involved in tumor progression and that the increased expression of caveolin-1 is a late event in urothelial carcinomas. 55 The increased expression of caveolin-1 is associated with tumor progression and poor prognosis in Figure 11.…”
Section: Discussionmentioning
confidence: 91%
“…ITGA4 is a good example. Even classical proto-oncogene c-src, whose activity or expression is elevated in a number of human tumors, suppresses metastasis of bladder cancer (56,57). Future work should therefore include metastatic models of carcinomas to evaluate whether HOPX is universally associated with metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Cav-1 acts as a scaffolding protein by interacting with signaling molecules through a caveolin scaffolding domain to modulate gene expression, signal transduction and protein translocation in the cell membrane (18 invasion and metastasis (19)(20)(21)(22). Additionally, it has been shown that Cav-1 is closely associated with the development of drug resistance (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%